SEASONAL SONGS IN UZBEK CHILDREN'S GAME FOLKLORE - Ilhom Shoymardonov Alixonovich (Scholar Express Journal, 2022)
This article is written about seasonal songs in Uzbek children's game folklore. When it comes to children's songs, it is appropriate to note that adults also participated in their creation. Because adults also participate in some games and songs intended for children. Some songs are performed by adults and children, as well as duet forms. For example, adults actively participate in the formation of children's relationship to nature. As a result, children have their own calendar and seasonal ritual songs that represent it.
Keywords: game; folklore; song; performance